The effect of hydrochloric acid and sodium hypochlorite on fracture resistance of orthodontic self-cure acrylic base - Saeed Noorollahian; Atefeh Tabibi (Wolters Kluwer Medknow Publications, 2022)
Background: Patient cooperation is necessary for treatment success in removable orthodontics. Every factor has an adverse effect on appliances appearance can impede appliance wearing. This study investigated the effect of immersion in household cleaner and bleach liquids on fracture resistance of self-cure orthodontic acrylic resins. Materials and Methods: This in vitro study two orthodontic acrylic resins (Megadental® and Acropars®) were used. Eighty identical acrylic samples (50 mm × 5 mm × 3 mm) from each acrylic resin were fabricated and divided into four groups (n = 20). For each type of acrylic resin; Group 1: 15 min immersion in household cleaner liquid (hydrochloric acid [HCl], 10%), 1 min rinsing with running water, 15 min immersion in household bleach liquid (sodium hypochlorite [NaOCl], 5.25%) and 1 min rinsing with running water were done. For Group 2, two times and for Group 3, three times immersion just like Group 1, were done. Group 4, as control, had no immersion. Fracture resistance of samples was measured with universal testing machine (Instron) in 3-point bending set-up. Data were analyzed with two-way repeated measurement ANOVA. Significance level was set at 0.05. Results: Fracture resistance of Acropars groups was greater than counterpart Megadental ones (P < 0.001). Immersion factor, alone (P = 0.375) and in combination with material (P = 0.603), did not make a significant difference among fracture resistance of each acrylic resin groups. Conclusion: 15 min immersion in household cleaner liquid (HCl acid) followed by 15 min immersion in household bleach liquid (NaOCl 5.25%) and even 3 times repetition of this process had not significant adverse effect on fracture resistance of acrylic resins.